Intraosseous lipoma of the calcaneum: a rare cause of heel pain - Mawardi, Maliza; Hussin, Paisal (FMS, 2018)
Heel pain is a common presentation at any outpatient clinic. Heel pain may originate from either bone or the surrounding soft tissues. Tendo achilles tendinitis and plantar fasciitis are the two most common causes of heel pain. We report a case of an uncommon condition presenting through a common presentation at the primary care clinic, i.e., an intraosseous lipoma of the calcaneum presenting through heel pain. This tumour constitutes 0.1% of benign bone tumours and is 8% prevalent in the calcaneum bone.